Analysis of pancreatic cyst fluid - Ngamruengphong, Saowanee (Surg Pathol Clin, 2016)
Pancreatic cysts are extremely common, and are identified in between 2% to 13% on abdominal imaging studies. The majority of pancreatic cysts are pseudocysts, serous cystic neoplasms (SCNs), mucinous cystic neoplasms (MCNs) or intraductal papillary mucinous neoplasm (IPMNs). The management of pancreatic cysts depends on whether a cyst is benign, has malignant potential, or harbors high-grade dysplasia or invasive carcinoma. The diagnosis of pancreatic cysts, and assessment of risk of malignant transformation, incorporates a number of factors including clinical history, computed tomography (CT), magnetic resonance imaging (MRI), endoscopic ultrasound and fine needle aspiration of cyst fluid (EUS-FNA). This paper reviews the cyst fluid markers which are currently used, as well as promising markers under development.